Investing In Education - Economic Policy Research Centre (Economic Policy Research Centre, 2021)
Due to the shift from sector based budgeting to programme based budgeting, the education sector lies under the human capital development programme. The brief therefore asseses the contribution of the education sector to the new HCD programmes as articulated in the NDPIII. The education sector is a critical component towards achieving human capital aspirations of building teachers and learners’ capacity as articulated in the recently approved third National Development Plan (NDP) III. Given the coronavirus pandemic and the associated school closures, ensuring that all formally enrolled children return to school will be critical during FY 2021/22.